PRELIMINARY QUALITATIVE FITOCHEMICAL STUDY AND QUANTIFICATION OF FLAVONOIDS AND TANNINS OF ETHANOLIC EXTRACT OF LEAVES OF Desmodium vargasianum Schubert - Rengifo Zevallos, Diana R. (2018)
In this work the secondary metabolites of Desmodium. vargasianum Schubert “pie de perro” leaves ethanolic extract was investigated. The phytochemical screening realized on the ethanolic extract suggests the presence of phenolic compounds (flavonoids, tannins) and alkaloids. The thin layer chromatography was positive for flavonoids, tannins and alkaloids. Finally, total flavonoids and total tannins were quantified. In the quantification of total flavonoids by UV-VIS spectrophotometry, 202,05 ± 1,10 mg QE/g of ethanolic extract (EE) was obtained. As for the total tannins quantification by UV-VIS spectrophotometry, 178,50 ± 0,75 mg TAE/g EE was obtained.